2015
DOI: 10.1159/000440995
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Decreases the Occurrence of Myocardial Fibrosis by Inhibiting the NADPH-ERK-NF-κB Pathway

Abstract: Objectives: The aim of this study was to investigate the protective role of erythropoietin (EPO) against myocardial fibrosis (MF). Methods: Pressure-overloaded rats were established by abdominal aortic constriction, the rats were randomly divided in a double-blind manner into 3 groups (n = 12 for each group): sham-operated rats (sham), operated rats receiving physiological saline (vehicle) and operated rats receiving 4,000 U/kg rhEPO (EPO group). The vehicle and drugs were administered to rats by intraperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Downstream inflammatory mediators of the TLR4 signaling pathway, including TGF-β1 ( 30 ), TNF-α, IL-6 ( 31 ), IL-1β, IL-17A ( 32 ), MMP-9 and MMP-2 ( 33 ), promote the occurrence and development of MF ( 22 ). In the present study, it was demonstrated that EPO significantly decreased the release of TGF-β1, TNF-α, IL-6, IL-1β and IL-17A in serum and inhibited the expression of MMP-9 and MMP-2 in myocardial tissue of MF in rats subjected to AAC, which was consistent with the findings presented in other reports ( 11 , 34 , 35 ). The effects of EPO on inflammatory mediators may be key in attenuating MF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Downstream inflammatory mediators of the TLR4 signaling pathway, including TGF-β1 ( 30 ), TNF-α, IL-6 ( 31 ), IL-1β, IL-17A ( 32 ), MMP-9 and MMP-2 ( 33 ), promote the occurrence and development of MF ( 22 ). In the present study, it was demonstrated that EPO significantly decreased the release of TGF-β1, TNF-α, IL-6, IL-1β and IL-17A in serum and inhibited the expression of MMP-9 and MMP-2 in myocardial tissue of MF in rats subjected to AAC, which was consistent with the findings presented in other reports ( 11 , 34 , 35 ). The effects of EPO on inflammatory mediators may be key in attenuating MF.…”
Section: Discussionsupporting
confidence: 93%
“…In our preliminary study, EPO had significant anti-inflammatory effects and attenuated fibrosis in a pressure-overload rat model that was subjected to abdominal aortic constriction (AAC) ( 10 ). Furthermore, it has been indicated that EPO may be a powerful cardioprotective agent and a potential component for antifibrotic therapies ( 11 13 ). The protective mechanism may be via inhibiting the secretion of inflammatory factors, including transforming growth factor (TGF)-β, the interleukin (IL) family, and tumor necrosis factors (TNFs) ( 11 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPO’s protective effect was described in a wide variety of processes in cardiovascular pathophysiology, particularly in ischaemia, cell proliferation, apoptosis, and platelet activation. EPO exhibited myocardial protection through the MAPK/ERK induced GATA-4 stability, reduction of caspase-3 activity, upregulation of Bcl-2 [ 94 ], and decreased myocardial fibrosis via suppressing the NADPH/ERK/NF-κB pathway [ 95 ]. Paracrine EPO accelerated the healing process in intramyocardial cardiac angiogenetic stem cells via the activation of AKT signaling and through the upregulation of upstream signals FOS and FZD7 in addition to the activation of TGF-β/WNT signaling [ 96 ].…”
Section: Epor/pi3k/akt and Epor/mapk In Non-hematopoietic Tissuesmentioning
confidence: 99%
“…Besides, the Rho/Rho-associated coiled-coil forming protein kinase (ROCK)/ NF-kB signaling pathway can be inhibited by crocetin ester to exert a cardioprotective effect against AMI (Huang et al, 2016). By targeting the nicotinamide adenine dinucleotide phosphate (NADPH)/extracellular regulated protein kinase (ERK)/NF-kB pathway, erythropoietin can inhibit rat cardiac fibroblast proliferation, transformation, and collagen deposition (Wang et al, 2016). Receptor-interacting protein (RIP140), as well as inhibitor of NF-kB (IkB)/NF-kB p65 (p65)/IL-6, can be regulated by glycyrrhizic acid to preserve heart function by increasing cardiac antioxidants and reducing cardiomyocytes apoptosis (Yang et al, 2017a).…”
Section: Pi3k-akt and Related Pathwaysmentioning
confidence: 99%